The large-scale implementation and evaluation of a healthy lifestyle programme in residential out-of-home care: study protocol. Issue 1 (31st December 2020) - Pizzirani, Bengianni; O'Donnell, Renée; Bruce, Lauren; Breman, Rachel; Smales, Madelaine; Xie, Jue; Hu, Hao; Skouteris, Helen; Green (nee Cox), Rachael
ABSTRACT: Young people living in out-of-home care (OoHC) are widely considered to be one of the most vulnerable groups in the community. This article describes the evaluation and implementation study protocol of a healthy lifestyle programme developed to improve the eating and physical activity habits of young people living in residential OoHC. The study will employ a longitudinal multi-group pre-post process evaluation to assess our implementation strategy in the dissemination of HEALing Matters at the: 1) system-level; 2) organizational-level; 3) residential home-level; and 4) individual-level (N = approximately 60 residential homes [approximately 400–500 staff and 240 young people]). Implementation- and program-related outcomes will be assessed using self-report surveys, semi-structured interviews and focus groups, house audits and website usage data collected prior, during and after implementation. Results are expected to inform and help guide the further development and training of residential care staff's understanding and application of health literacy.